Waste disposal and recycling practices in educational institutions - Lee, Shirley Shiat Ai. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Every year, large quantities of waste of wastes are generated, varies from industrial wastes to institutional wastes. The waste creates environmental problems in many kids. The scenario accessed from the study shows the rate of waste generated per capita per day (recess time) was at 60 g with the highest amount waste recorded was dominated by plastic bags. They recycling rate is at moderate level as many aware of the recycling concept regardless of their location or education level. Study also showed that the recycling rate in rural schools were higher than urban schools.